Evidence for the Presence of Insulin-Dependent Diabetes-Associated Alleles on the Distal Part of Mouse Chromosome 6 - Melanitou, Evie; Joly, Florence; Lathrop, Mark; Boitard, Christian; Avner, Philip (Genome Research, 1998)
Type 1 diabetes (IDDM) is a complex disorder with multifactorial and polygenic etiology. A genome-wide screen performed in a BC1 cohort of a cross between the nonobese diabetic (NOD) mouse with the diabetes-resistant feral strain PWK detected a major locus contributing to diabetes development on the distal part of chromosome 6. Unlike the majority of other Idd loci identified in intraspecific crosses, susceptibility is associated with the presence of the PWK allele. Genetic linkage analysis of congenic lines segregating PWK chromosome 6 segments in a NOD background confirmed the presence of theIdd locus within this region. The genetic interval defined by analysis of congenic animals showed a peak of significant linkage (P = 0.0005) centered on an ∼9-cM region lying between D6Mit11 and D6Mit25 genetic markers within distal mouse chromosome 6.[Genetic markers polymorphic between the NOD and PWK strains are available as a supplement athttp://www.genome.org]